2018
DOI: 10.1108/ilt-05-2018-0197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen on graphene growth from solid waste products by chemical vapour deposition: friction coefficient properties

Abstract: Purpose The purpose of this paper is to study the effect of hydrogen (H2) gas on the graphene growth from fruit cover plastic waste (FCPW) and oil palm fibre (OPF), as a solid feedstock, towards the coefficient of friction (COF) properties. Design/methodology/approach Graphene film growth on copper (Cu) substrate was synthesised from FCPW and OPF, as a solid feedstock, using the chemical vapour deposition (CVD) method, at atmospheric pressure. The synthesised graphene was characterised using Raman spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A study performed by Tahir N.A.M et al confirmed the tribological effects of graphene growth from oil palm fiber [188]. They concluded that the presence of graphene on top of the substrate could reduce the coefficient of friction.…”
Section: Application Of Carbon-based Nanostructured Materials Derived...mentioning
confidence: 92%
See 1 more Smart Citation
“…A study performed by Tahir N.A.M et al confirmed the tribological effects of graphene growth from oil palm fiber [188]. They concluded that the presence of graphene on top of the substrate could reduce the coefficient of friction.…”
Section: Application Of Carbon-based Nanostructured Materials Derived...mentioning
confidence: 92%
“…Mat Tahir et al made another attempt to synthesize graphene using a different substrate to anneal the graphene [188,189]. The research was done using oil palm fibers at 1020 °C inside a CVD reactor.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%